PENGARUH PROMOSI JABATAN DAN MASA KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM KABUPATEN OKU - Titie Syahnaz Natalia; Dyah Ayu Putriani; Nourma Wulanda; Dona Aulia Ananda (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
This research discussed the influence of job promotion and working period on jobsatisfaction of employees in the Regional Drinking Water Company of OKUdistrict. The data collection technique used in this research was through thedistribution of questionnaires. The population was 66 people. The data analysistechnique used was Multiple Linear Regression. Based on the partial analysisresults, there was an influence of job promotion on job satisfaction of employeesin the Regional Drinking Water Company of OKU district with a t-value of 2.676.The working period variable had an influence on job satisfaction of employees inthe Regional Drinking Water Company of OKU district with a t-value of 7.073.Simultaneously, there was an influence of job promotion and working period onjob satisfaction of employees in the Regional Drinking Water Company of OKUdistrict with an F-value of 86,776. The coefficient of determination (R2) obtainedwas 0.734. This indicated that the contribution of the influence of job promotionand working period on job satisfaction was 73.4%, while the remaining 26.6%was influenced by other variables outside of the research such as education, workexperience, perception, and work attitude (Mangkunegara, 2015:120).